2013
DOI: 10.3892/ijmm.2013.1519
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical basis of cancer chemoprevention and/or chemotherapy with ginsenosides (Review)

Abstract: Cancer still imposes a global threat to public health. After decades of research on cancer biology and enormous efforts in developing anticancer therapies, we now understand that the majority of cancers can be prevented. Bioactive phytochemicals present in edible plants have been shown to reduce the risk of various types of cancer. Ginseng (Panax ginseng C.A. Meyer), which contains a wide variety of saponins, known as ginsenosides, is an age-old remedy for human ailments, including cancer. Numerous laboratory-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 104 publications
(120 reference statements)
0
26
0
Order By: Relevance
“…To increase survival rates and improve quality of life, novel natural medicines are required to treat T-ALL. GRh2 and GRg3, extracted from the root of the Panax ginseng , are recognized as major active anticancer saponins in ginsenosides (23). GRg3 may be metabolized to GRh2 by human fecal microflora (24).…”
Section: Discussionmentioning
confidence: 99%
“…To increase survival rates and improve quality of life, novel natural medicines are required to treat T-ALL. GRh2 and GRg3, extracted from the root of the Panax ginseng , are recognized as major active anticancer saponins in ginsenosides (23). GRg3 may be metabolized to GRh2 by human fecal microflora (24).…”
Section: Discussionmentioning
confidence: 99%
“…8 These "natural substances" are low-molecular weight organic compounds found in plants that activate a defence system against physiological and/or environmental stress. [9][10][11] Such compounds have antioxidant, antimicrobial, and immunomodulatory properties and derive from secondary metabolites, which belong mainly to the category of terpenes, terpenoids, alkaloids, phenols, and flavonoids. [12][13][14] Polyphenols compound are secondary metabolites widely distributed in the plant kingdom, with many biological properties, antiallergic, antiatherogenic, anti-inflammatory, antimicrobial, and antioxidant.…”
mentioning
confidence: 99%
“…The antioxidative property of natural agents will show the therapeutic and preventive effect on the process of carcinogenesis, such as the natural antioxidants ginsenosides and curcumin [27, 28]. Our recent work has reported that D. candidum could prevent MNNG-induced gastric cancer [19].…”
Section: Discussionmentioning
confidence: 99%